Development of a Simple Assay Protocol for High-Throughput Screening of Mycobacterium tuberculosis Glutamine Synthetase for the Identification of Novel Inhibitors - Singh, U.; Panchanadikar, V.; Sarkar, D.
Mycobacterium tuberculosis glutamine synthetase (GS)is an essential enzyme involved in the pathogenicity of the organism. The screening of a compound library using a robust high-throughput screening (HTS)assay is currently thought to be the most efficient way of getting lead molecules, which are potent inhibitors for this enzyme. The authors have purified the enzyme to a >90
Keywords: GLUTAMINE SYNTHETASE; HIGH-THROUGHPUT SCREENING; MYCOBACTERIUM